Design and Development of The Data Requestand Statistical Service (Tanya Akses Statistik/TANGKIS) Website Information System with an Automatic Email Notification Feature at the Central Bureau of Statistics of East Lampung Regency - Siti Amanaturtohmah; Imam Mualim; Nuari Anisa Sivi (Al-Makki Publisher, 2026)
The Integrated Statistical Service (PST) at BPS East Lampung Regency handles a high volume of data requests from researchers, government agencies, students, and private institutions through its front-line channel, TANGKIS. This service currently relies on walk-in visits, manual logbook recording, and unstructured WhatsApp or email correspondence, causing delayed processing, inconsistent follow-up, difficult status tracking, and the absence of formal notification when requested data is ready. This study aims to design and develop a web-based TANGKIS information system with an automatic email notification feature to digitize and streamline the request workflow. The system was developed using the SDLC Waterfall model, with UML-based design, PHP and Laravel implementation, a MySQL database, and PHPMailer integrated with SMTP, then evaluated through Black Box Testing and a dedicated notification reliability assessment. Black Box Testing of 20 functional features achieved 100% validity, while 30 simulated requests reached a 100% email delivery rate with an average latency of 4.8 seconds, reducing data-readiness awareness time from one to three days to under one minute. These results imply that a low-cost, event-driven email notification architecture can meaningfully strengthen the efficiency, transparency, and responsiveness of statistical public service, supporting the digital transformation of regional government statistical services.